The Role of The State Towards Victims of Electronic‐Based Sexual Violence in Law No. 12 Years 2022 - Allan Rendra Prana Pratama Ramadhan; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2023)
Sexual violence is a complex reality that immensely affects the integrity of human dignity for victims. Victims of sexual violence, mostly women and girls, show that there is a gender discriminatory construction issue in society that affects the problem of legal protection both in abstracto and in concreto. There are 3 (three) problems in this paper, such as: First, what is the current condition of protection for victims of sexual violence? Second, what is the current form of the policy on sexual violence protection in Indonesia? Third, how is the criminal law policy to protect victims of sexual violence based on Pancasila justice? This research is juridical‐normative through a literature study using legal materials, and then the descriptive analysis is completed to answer the problems. Based on the results of the discussion, it is concluded that the legal protection of victims of sexual violence is indeed hampered by factors of legal substance, structure, and culture. The current form of policy to protect victims of sexual violence is not nonetheless comprehensive and responsive to victims. The Act on the Crime of Sexual Violence (UU TPKS) as part of the reform of criminal law policies has maintained a progressive basis in terms of protection, undertaking, and recovery of victims. There are indeed substantive issues that have the potential to reduce the strengthening of protection for victims of sexual violence such as the absence of norms regarding rape, forced abortion and integration with other laws as a consequence of the existence of bridge articles.